Adaptation and auteurism in South Asian Studies with reference to Rabindranath Tagore’s Works on Screen - Ahmed, Shah; Hasan, Md. Mahmudul; Ramlan, Wan Nur Madiha (2020)
Since its inception in the 1890s, cinema has been predominantly contingent upon literature for its source, growth and success. The curiosity to know what happens when a literary text is rendered into visual medium has led to a myriad of debates and discussions. Unlike in Europe and North America, in South Asia cinematic translation of literature has not received substantial scholarly attention and critical insights. As a result, the literary adaptations of Bengali authors are hardly discussed from the theoretical perspectives of adaptation studies. Contextualising adaptation studies in South Asia, especially in India and Bangladesh, this paper recommends the incorporation of auteurism in adaptation studies and argues that, like literary authors, artistic filmmakers (read adapters) are the authors of their films. It attempts to wean away adaptation discourse from the outmoded fidelity/infidelity debate and maintain that directorial transgression is an essential modality in the dynamics of literary adaptation for a successful intermedial rendition. In distinguishing auteurs from general adapters, we suggest that some of the adapting directors, especially those of Rabindranath Tagore’s works, can be evaluated from the auteurist premise of creative independence, technical competence and artistic imagination.